[Wielkanocna karta okolicznościowa z twarzą w ciemnych okularach] . Easter greeting card with a face in sunglasses - Solidarność Toruń. (Solidarność Toruń)
Green and red print print on white paper, with undivided back. Easter greeting card contains graphic image which represents a male face with spectacles which have Easter eggs instead of glasses, with captions "Joyful Easter Eggs" and "Halleluj-ah".